Society of Toxicologic Pathology Nonhuman Primate Special Interest Group*: Idiopathic Femoral Head Chondrolysis in Nonclinical Research Macaques. (July 2022) - Magagna, Michelle A.; Beazley, Shelley L.; Veenstra, Jesse W.; Newell, Michelle A.; Patrick, Daniel J.
Idiopathic femoral head chondrolysis is a recognized condition in human adolescents and has previously been reported in two macaques at a biomedical research facility. A cluster of coxofemoral joint abnormalities consistent with this condition affecting seven cynomolgus macaques over a four-month period in 2016 and 2017 was observed at a single, nonclinical contract research facility, prompting enhanced physical examination screening efforts during animal receipt and pre-study evaluation to identify additional affected animals. This article summarizes the results of this investigation from November 2016 to March 2021, yielding 97 total cases for an overall incidence of 0.54% (97/17, 898 macaques). Affected animals were presented with one or more of the following unilateral or bilateral findings on physical examination and/or diagnostic imaging: lameness, palpable coxofemoral joint abnormalities, femoral head atrophy with variable loss of articular cartilage and irregularity of the femoral head surface, enlarged joint space with effusion, and increased radiographic density of the femoral head. This condition prevented use of affected animals on study for 54% of the cases (52/97 animals). Recognition of this idiopathic condition is important in drug safety evaluation studies to distinguish it from test article–related effects.